2014
DOI: 10.1007/s00217-014-2163-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of French fries processing on the glycoalkaloid content in coloured-fleshed potatoes

Abstract: The mean values were about 97.5 % in ready-to-eat French fries. In French fries after I and II steps of frying, the ratio α-solanine to α-chaconine was lower (1.0:2.0) than in unpeeled potatoes (1.0:2.3).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
1
17
0
2
Order By: Relevance
“…Previous chromatography-based methods to quantify both potato and tSGAs relied on photodiode array detectors set to 208 nm (Kozukue and Friedman, 2003;Kozukue et al, 2004;Tajner-Czopek et al, 2014;Del Giudice et al, 2015). Given that the molar extinction coefficient for alpha-tomatine is only 5000 M −1 c −1 , (Keukens et al, 1994), photodiode array detectors are often not sensitive enough for detecting low quantities of these compounds, nor distinguishing between different alkaloids.…”
Section: Lod and Loqmentioning
confidence: 99%
“…Previous chromatography-based methods to quantify both potato and tSGAs relied on photodiode array detectors set to 208 nm (Kozukue and Friedman, 2003;Kozukue et al, 2004;Tajner-Czopek et al, 2014;Del Giudice et al, 2015). Given that the molar extinction coefficient for alpha-tomatine is only 5000 M −1 c −1 , (Keukens et al, 1994), photodiode array detectors are often not sensitive enough for detecting low quantities of these compounds, nor distinguishing between different alkaloids.…”
Section: Lod and Loqmentioning
confidence: 99%
“…Previous chromatography-based methods to quantify both potato and tSGAs relied on photodiode array detectors and set 208 nm (Del Giudice et al, 2015; Kozukue et al, 2004; Kozukue and Friedman, 2003; Tajner-Czopek et al, 2014). Given that the molar extinction coefficient for alpha-tomatine is only 5000 M -1 c -1 , (Keukens et al, 1994), photodiode array detectors are not sensitive enough for detecting low quantities of these compounds, nor distinguishing between different alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…According to Friedman & McDonald (), the temperature that is necessary for a significant decrease in glycoalkaloid quantities is 170–180 °C. This statement is confirmed by some other authors (Rytel et al ., ; Friedman, ; Pęksa et al ., ; Tajner‐Czopek et al ., , ) who observed that glycoalkaloid losses after the frying process ranged from 30% to 40%, whereas the nitrate V losses were 83% to 85%. Moreover, the studies here showed that in the ready‐to‐eat product, 2.93 mg/100 g (approximately 10% of the initial) glycoalkaloid content (10% chaconine, 11% solanine) and 134 mg NaNO 3 kg −1 , which was 31% of the initial nitrates (Tables ), remained.…”
Section: Resultsmentioning
confidence: 99%